Radical DIFC reforms update trust law and extend wealth planning options. Issue 2 (23rd January 2019) - Stibbard, Paul
Abstract: The Dubai International Financial Centre ('DIFC') is a special zone within Dubai, with its own common law jurisdiction. It remains an integral part of Dubai. The DIFC Courts are part not only of the Dubai Courts but also of the federal United Arab Emirates ('UAE') judicial system. On 21 March 2018, the DIFC enacted the Trust Law No 4 of 2018 ('the Trust Law'). This superseded the Trust Law No 11 2005. One of its primary aims is to bring DIFC Trust Law in line with international best practice. While many of the changes draw on developments from a number of trust jurisdictions, the main provisions follow the US Uniform Trust Code ('UTC'). The Trust Law contains updated provisions on quite a number of different issues, including those covered by this article.